Teacher Self-Actualization and Professionalism in the 21st Century Education Era (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
21st century education requires teachers to be able to self-actualize in order to improve their professionalism. Self-actualization is a process in which individuals reach their full potential through personal and professional development. Every individual has diverse potentials and with full awareness can be utilized as well as possible so that they can be actualized properly. Likewise with teachers, they need space to actualize all their potential in order to produce maximum learning. This research uses the literature study method to examine the relationship between teacher self-actualization and professionalism in the context of modern education. The results show that self- actualization contributes to increased teacher creativity, engagement and self-efficacy, which in turn improves student learning outcomes. Factors such as support from school leaders, continuous professional development, and a positive work environment play an important role in supporting teachers' self-actualization process. This research provides strategic insights for creating an educational ecosystem that supports teacher development, both individually and collectively, to meet the increasingly complex challenges of 21st century education.